Statistical distribution of pentad rainfall over India during monsoon season - MOOLEY , D A.; RAO, G. APPA (MAUSAM, 1970)
Statistical distribution of pentad rainfall during southwest and northeast monsoon seasons, at representative stations in India, has been studied" From the histograms it is seen that these distributions are right (positive) skewed" Gamma distribution function has been fitted to rainfall data and the guess of fit of the distribution to the rainfall data has been tested by Chi-square tests. These tests show that pentad rainfall may be described by Gamma distribution.